PERSEPSI MAHASISWA PERHOTELAN AKADEMI PARIWISATA DENPASAR TERHADAP PEMBELAJARAN BAHASA JEPANG DAN BAHASA INGGRIS - Ni Putu Sri Utami Putri; Eka Anastasia Wijaya (Jurnal Kajian dan Terapan Pariwisata, 2024)
This research is designed to describe D3 Hospitality Denpasar Academy of Tourism students’ perception toward foreign language learning especially Japanese and English to maximize the process of foreign language learning. Framed within a qualitative design, this study employed observation, survey, and interview methods with an observation sheet, a questionnaire, and an interview guide as the instruments to collect the data. The study results showed that the student’s perception of foreign language learning was that Japanese is more difficult than English. It was because the students found more challenges in writing and pronunciation during the learning process of Japanese. Further, it was affected by the learning frequency, in which English is being learned from elementary to higher education levels. Meanwhile, Japanese is only learned at the higher education level and the application of Japanese in daily life tends to be limited. This indicates that limited learning of foreign languages other than English has a major influence on perception of learning a foreign language.